Translating legislative documents at the European Parliament: e-Parliament, XML, SPA and the Cat4Trad workflow - Chartier-Brun, Pascale (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2018)
The translation services at the European Parliament, under the Directorate-General for Translation, use a chain of applications – e-Parliament – and XML technologies for the automation of the translation of legislative texts and efficient reuse of translated segments. This paper presents a detailed look at the translation workflow implemented at the European Parliament with focus on Safe Protocol Automation (SPA) and the Cat4Trad translation environment. Die Übersetzungsdienste des Europäischen Parlaments, unter der Generaldirektion Übersetzung, nutzen eine Kette von Anwendungen – e-Parliament – und XML-Technologien für die Automatisierung der Übersetzung von Rechtstexten und zur effizienten Wiederverwendung von übersetzten Segmenten. Dieser Beitrag bietet einen detaillierten Einblick in den Übersetzungsworkflow im Europäischen Parlament mit dem Fokus auf Safe Protocol Automation (SPA) und der Cat4Trad Übersetzungsumgebung. Les services de traduction du Parlement européen, sous la Direction générale de la traduction, utilisent une chaîne d’applications – e-Parliament – et les technologies XML pour l’automatisation de la traduction des textes législatifs et la réutilisation efficace des segments traduits. Cet article présente un regard détaillé sur le processus de traduction au Parlement européen, en mettant l’accent sur Safe Protocol Automation (SPA) et l’environnement de traduction Cat4Trad.
Keywords: Europäisches Parlament; Übersetzungsworkflow; mehrsprachige EU; XML; Cat4Trad, legislative Dokumente; e-Parliament; maschinelle Übersetzung; juristische Übersetzung, Übersetzungsspeicher; Konkordanz; Euramis